Analysis of students’ numeracy skill in genetics topic based on minimum assessment competency - Listia Andriani; Sariwulan Diana; Topik Hidayat (Department of Biology Education, Universitas Pendidikan Indonesia, 2022)
Genetics is a biology topic that applies several mathematics principles. It causes numeracy skills in genetics to be important for students. Therefore, a good mastery of numeracy skills could help students to solve genetics problems and achieve genetics competencies. Based on this statement, this study was conducted to analyze the numeracy skills of class XII based on the Minimum Competency Assessment (Asesmen Kompetensi Minimum/AKM). Fifty-four students were involved as research participants. Furthermore, 30 questions were used in this study. The result showed that the numeracy skills of class XII were still in the low category due to the lack of experience in solving AKM-type questions, learning experience, mathematics ability, mastery of genetics concepts, and students' perceptions of genetics. The low students’ performance on numeracy skills should be considered especially by an education provider to adjust the learning implementation that can improve students’ numeracy skills in genetics.